Advances in combining gene therapy with cell and tissue engineering-based approaches to enhance healing of the meniscus. Issue 8 (August 2016) - Cucchiarini, M.; McNulty, A.L.; Mauck, R.L.; Setton, L.A.; Guilak, F.; Madry, H.
Summary: Meniscal lesions are common problems in orthopaedic surgery and sports medicine, and injury or loss of the meniscus accelerates the onset of knee osteoarthritis (OA). Despite a variety of therapeutic options in the clinics, there is a critical need for improved treatments to enhance meniscal repair. In this regard, combining gene-, cell-, and tissue engineering-based approaches is an attractive strategy to generate novel, effective therapies to treat meniscal lesions. In the present work, we provide an overview of the tools currently available to improve meniscal repair and discuss the progress and remaining challenges for potential future translation in patients.